KARAKTERISTIK FISIK TEPUNG TEH HIJAU YANG DIPROSES MENGGUNAKAN MESIN DISC MILL DAN STONE MILL - M. Iqbal Prawira-Atmaja; Shabri Shabri; Sugeng Harianto; Hilman Maulana; Dadan Rohdiana (Jurnal Teknologi dan Industri Pangan, 2018)
Size reduction could affect the physical properties of green tea powder. The aim of this study was to determine the physical properties of green tea powder processed by different milling methods. A disc mill (DM) with single screw made from stainless steel and a stone mill (SM) made from granite stone were used to produce green tea powder. Water holding capacity, water solubility index, swelling capacity, wettability, extraction yield, dispersibility and dispersion stability, and particle size distribution were analyzed to determine the physical properties of green tea powder. The morphology and shape of green tea powder were also observed using scanning electron microscopy. The DM method produced green tea powder with higher values of water absorption index, swelling capacity and water holding capacity, i.e. 4.57 g/g; 5.17 mL/g; and 6.18 g/g respectively. Green tea powder with SM method had a brighter color with L value of 60.1 and was a fine powder with d50 of 1.4 µm. Based on the above physical properties, green tea powder with SM milling method is more suitable as food products.